MODEL TERAPI TARI BALI SEBAGAI METODE INTERVENSI SOSIAL UNTUK PENANGANAN KORBAN KEKERASAN SEKSUAL DALAM RUMAH TANGGA (Studi Kasus Pada Keluarga NS di Kabupaten Gianyar, Propinsi Bali) - P, Elisabeth Endang (Jurnal Insani, 2016)
This paper will discuss the research findings of a Balinese Dance Therapy model as a new interventionstrategy. This model uses Balinese traditional dance as an intervention method. The study was conducted inBali. It involved one participant who experienced sexual violence: husband as the actor and the wife as thevictim. The research uses a qualitative study method. As the result of this study, the writer found thatthrough this therapy model, the interaction between the husband and the wife can be re-harmonized, as theybuild a better and meaningful life. As the conclusions, Balinese dance movements involved in the package ofdance therapy model can be used as a therapy for the purposes of: (1) Rebuilding human relations in the“disturbed” family to regain the harmonious family life; (2) Achieving a self balancing family for a betterlife.